Wage-setting and gender pay equality in Australia: Advances, retreats and future prospects. (September 2020) - Smith, Meg; Whitehouse, Gillian
This article re-examines the main principle applied in the pursuit of gender equality in Australian wage-setting systems (equal remuneration for work of equal value) through the lens of a typology of contrasting approaches to gender (and overall) wage equality. It focuses on landmark legislative initiatives and cases over four epochs in Australian wage-setting history, from the first national equal pay case in 1969 to current provisions under the Fair Work Act. Our analysis indicates that there is no guarantee of a progressive trajectory, from narrowly conceived strategies that limit comparisons to the same work, through the revaluation of female-dominated work, to a more comprehensive approach capable of redressing systemic disadvantage. Rather, the Australian pattern has been one of advances, retreats and constantly changing barriers. We argue that although the principle of equal remuneration for work of equal value has potential to challenge the reproduction of gender inequalities within wage-setting systems, this is highly contingent on the strategies in place and ultimately requires recognition that wage disparities reflect the accumulation of structural inequalities and gendered practices.